The S-Transform of Distributions - Sunil Kumar Singh (The Scientific World Journal)
Parseval’s formula and inversion formula for the S-transform are given. A relation between the S-transform and pseudodifferential operators is obtained. The S-transform is studied on the spaces 𝒮(ℝn) and 𝒮′(ℝn).